Verbrauchermacht in Bewegung Protest, Politik und sozio-technische Infrastrukturen - Hohnsträter, Dirk; Krankenhagen, Stefan; Lamla, Jörn (Verbraucherforschung, 2022)
Consumers can influence markets through their consumption behaviour-whether by consciously choosing or rejecting certain products and consumption patterns, or by loudly protesting, for example in demonstrations against climate change. But how far does the power of consumers extend? How capable of conflict are they in the face of often heterogeneous interests, differing objectives and, at best, weakly developed group identities? What forms of interest articulation are available and how are they used? What role do consumer policy, companies and the digital revolution play in this regard? This volume documents the fifth annual conference of the Consumer Research Network. With contributions by Dr. Holger Backhaus-Maul, Prof. Dr. Kai Uwe Hellmann, Prof. Dr. Christian Kastrop, Dr. Annekathrin Kohout, Prof. Dr. Jörn Lamla, Dr. Alexander Sedlmaier, Prof. Dr. Holger Straßheim, Prof. Dr. Christoph Strünck, Maria Ullrich, M.A. and Dr. Katharina Witterhold.